Studi instrumen emisi debu tipe durag D-R 290 dalam menentukan karakteristik debu hasil pembakaran klinnker di Indarung V PT. Semen Padang (The study of the D-R 290 durag type dust emission instrument in determining the characteristics of dust from combustion clinics at Indarung V PT. Semen Padang ) - Desti Liala Kurnia; - Asrizal; Zulhendri Kamus (Department of Physics – Universitas Negeri Padang UNP, 2018)
Information about the measurement of dust and processing of measurement data needs to be known. But the reality shows that the information on dust emission instruments and processing data is still lacking. With this basis, research on dust emission instruments and processing of measurement data needs to be done. The research method used in this study is a descriptive research method with a quantitative approach in which the object of research is an instrument of dust emissions. The procedure of this study is in accordance with the steps for descriptive research. The results of this study indicate that the average measurement results of dust emissions with an hourly measurement range still provide measurement results below the specified limit limit. The threshold is based of Environment Regulation LHK No. 19 of 2017 concerning emission quality standards for cement industry businesses and / or activities, namely 75 mg/Nm3. Measurement for 6 months with a weekly measurement range of 25 weeks, obtained an average value of the results of the measurement of dust density of 18.96 mg/Nm. Dust density is directly proportional to the level of translucency, the larger the dust density, the higher the translucency level will also be.